Compliance with standard norms in collection, segregation and transport of biomedical waste in a tertiary care hospital: a cross-sectional study - Malgaonkar, Aniruddha A.; Kartikeyan, S. (International Journal of Research in Medical Sciences, 2016)
Background: This cross-sectional study was conducted to determine the gaps between the stipulated procedures for collection, segregation and transportation of bio-medical waste (BMW) and the actual practices; the levels of BMW-related awareness and training status of hospital employees; the protocols for occupational exposure to hazardous BMW and their implementation; and to recommend corrective measures. Methods: Primary data were collected by interviewing the staff in-charge of all BMW generating units of a tertiary care hospital and by recording information by direct on-site observation on a checklist. The participant’s confidentiality was maintained throughout the study. Results: The interviews and actual observations in 26 BMW generating units (out-patient departments, in-patient wards, laboratories, operation theatres, post-mortem room) revealed availability of trained person in-charge for BMW (3.85%), mixing of infectious and non-infectious waste at point of generation (73.07%), untreated syringes sent for final disposal (60.86%), availability of colour-coded bags (50%) and absence of puncture-proof containers (85.71%). 84.61% of interviewees reported having taken tetanus and hepatitis B immunizations. Conclusions: The necessary interventions include periodic training and re-training of personnel, active supervision of BMW handlers to enforce the use of protective gear and vaccination of all staff against tetanus and hepatitis B. Periodic BMW audit would be essential to determine the trends in the diversity and quantities of waste produced in health care settings and facilitate administrators to devise strategies for improved management of BMW.